2008
DOI: 10.1002/ps.1667
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of acephate, chlorpyrifos, cypermethrin and their metabolites in a humid‐tropical vegetable production system

Abstract: The dissipation of pesticides and their metabolites in the vegetable was rapid and faster than the dissipation in temperate climates. The degradation rates of pesticides in the soil were equal to or slightly faster than the degradation rates in temperate soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 26 publications
(46 reference statements)
4
25
2
Order By: Relevance
“…Residue in cauliflower was found to be 6.7 ± 1.8 at 0 and 0.12 ± 0.01 mg kg -1 at 15 days, respectively after application. Residue of cypermethrin in bean and cauliflower was found to be below MRL on 10 and 7 days after applicatio results are in agreement with the findings of Chai (2009) 6 and Nahar et al cypermethrin was studied in green mustard and tomato, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Residue in cauliflower was found to be 6.7 ± 1.8 at 0 and 0.12 ± 0.01 mg kg -1 at 15 days, respectively after application. Residue of cypermethrin in bean and cauliflower was found to be below MRL on 10 and 7 days after applicatio results are in agreement with the findings of Chai (2009) 6 and Nahar et al cypermethrin was studied in green mustard and tomato, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the lower dissipation of imidacloprid in the microcosm experiment compared to the acute toxicity tests might be due to UV light absorption by natural organic matter and suspended particulate matter in microcosms which decreases the photodegradation of imidacloprid (Lu et al, 2015). The dissipation was, however, found to be faster in the present sub-tropical study compared to earlier model and acute studies suggests that the dissipation is higher in the tropics than in temperate region due to higher temperature (28.2 ± 2 °C for microcosm experiment and 27.4 ± 0.6 °C for acute toxicity tests) and photodegradation during the experimental period (Laabs et al, 2007;Chai et al, 2009;Sánchez-Bayo and Hyne, 2011). In the present study, however, we found a buildup of imidacloprid concentrations in later applications in all treatment levels as compared to the first application in microcosm study.…”
Section: Fate Of Imidaclopridcontrasting
confidence: 75%
“…In case of double the recommended dose, residue was found to be 0.55 ppm at zero day which was slightly higher than the MRL value and was reduced to below MRL value (0.45 ppm) the following day (1 day) and declined to 0.01 ppm after 15 days of spraying. 7 where dissipation of cypermethrin was studied in green mustard and soil in a humid-tropical vegetable production system. Any pesticide including cypermethrin should get registration eligibility for using in a particular country both for agricultural and non-agricultural purposes after conducting human health and ecological risk assessment with positive results.…”
Section: Resultsmentioning
confidence: 99%